1992
DOI: 10.1111/j.1365-2249.1992.tb03059.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of tumour necrosis factor production in cells at the materno/fetal interface in human pregnancy

Abstract: SUMMARY Biologically active tumour necrosis factor (TNF) was detected in medium conditioned by incubation with cxplants of human pregnancy decidua or fetal chorionic villous tissue, taken in the first trimester and at term. Addition of endotoxin increased TNF release in most cases. ELISA assays gave similar results for TNF–α and also demonstrated low levels of TNF–β. Using cell populations purified by flow cytometry, secretion of biologically active TNF was shown to be localized to the macrophages. Cytotrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(23 citation statements)
references
References 33 publications
2
19
0
2
Order By: Relevance
“…TNF-α has been localized to proliferating trophoblast cells in villous tips, interstitial and endovascular EVT in the placental bed (Chen et al, 1991;Pijnenborg et al, 1998), and to a number of decidual cell types including T cells, uNK cells (Jokhi et al, 1994), stromal cells, macrophages (Vince et al, 1992) and endothelial cells (Tabibzadeh, 1991).…”
Section: Tnf-αmentioning
confidence: 99%
“…TNF-α has been localized to proliferating trophoblast cells in villous tips, interstitial and endovascular EVT in the placental bed (Chen et al, 1991;Pijnenborg et al, 1998), and to a number of decidual cell types including T cells, uNK cells (Jokhi et al, 1994), stromal cells, macrophages (Vince et al, 1992) and endothelial cells (Tabibzadeh, 1991).…”
Section: Tnf-αmentioning
confidence: 99%
“…This result is consistent with previous studies. 23,24 COX-2 is an inducible enzyme that is up-regulated by the inflammatory responses. It is involved in LPSand glucocorticoid-induced PTD.…”
Section: Placental Inflammation In Ptd Placentamentioning
confidence: 99%
“…57 TNFα mRNA and protein are prominent in macrophage-like cells present in term placentas and extraplacental membranes. 26,29 TNF-R1 mRNA is also present in high amounts in the villous stroma and endothelial cells, and to a lower extent in the syncytiotrophoblasts of the term placenta. 49 In cultured third trimester villous cytotrophoblasts, cytotoxic effects of TNFα, both alone and in combination with IFNγ, have been demonstrated, predominantly induced through TNF-R1.…”
Section: Systemic and Placental Levels Of Tnfα And Its Receptors In Pmentioning
confidence: 99%
“…26,27 Both TNF-Rs follow a similar pattern, with the highest expression in the late secretory phase. 28 Following decidualisation, TNFα mRNA has been shown to be present in macrophages, 29 T-cells, 30 uterine NK cells, endothelial cells, 31 and decidual stromal cells TNFα receptors in pregnancy in vitro. 32,33 Other studies have also shown that various decidual cell types express TNF-Rs.…”
Section: Tnfα and Its Receptors During The Normal First Trimestermentioning
confidence: 99%